Recent Progress in Intelligent Wearable Sensors for Health Monitoring and Wound Healing Based on Biofluids - Cheng, Siyang; Gu, Zhen; Zhou, Liping; Hao, Mingda; An, Heng; Song, Kaiyu; Wu, Xiaochao; Zhang, Kexin; Zhao, Zeya; Dong, Yaozhong; Wen, Yongqiang (Frontiers in Bioengineering and Biotechnology, 2021)
The intelligent wearable sensors promote the transformation of the health care from a traditional hospital-centered model to a personal portable device-centered model. There is an urgent need of real-time, multi-functional, and personalized monitoring of various biochemical target substances and signals based on the intelligent wearable sensors for health monitoring, especially wound healing. Under this background, this review article first reviews the outstanding progress in the development of intelligent, wearable sensors designed for continuous, real-time analysis, and monitoring of sweat, blood, interstitial fluid, tears, wound fluid, etc. Second, this paper reports the advanced status of intelligent wound monitoring sensors designed for wound diagnosis and treatment. The paper highlights some smart sensors to monitor target analytes in various wounds. Finally, this paper makes conservative recommendations regarding future development of intelligent wearable sensors.